1991
DOI: 10.1177/1046496491222001
|View full text |Cite
|
Sign up to set email alerts
|

Time, Interaction, and Performance (TIP)

Abstract: This article presents a theory of groups. The theory takes a more molarperspective on groups than has often been the case in group research. It gives special emphasis to temporal processes in group interaction and task performance. The three main sections of the article present the theory as a series of propositions about the nature of groups, temporal processes in group behavior, and temporal aspects of interaction, respectively. The final section presents brief comments on some implications and potential app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
903
2
16

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 985 publications
(935 citation statements)
references
References 23 publications
14
903
2
16
Order By: Relevance
“…Following methods used in psychology to study individual intelligence, Woolley et al [8] investigated the possibility of a collective intelligence factor: a latent factor describing a team's general ability to perform on a wide variety of tasks. They brought teams into the laboratory, had them perform a wide variety of tasks [6,9], and found that a team's performance on one type of task was closely related to its performance on all types. When they calculated a collective intelligence score based on the team's performance on the set of tasks, they found that it was only moderately related to the individual members' intelligence scores and was more predictive of future team performance than was individual members' average intelligence score [8] A series of studies have revealed factors related to collective intelligence, providing some insight into how to more reliably cultivate smart teams.…”
Section: Collective Intelligencementioning
confidence: 99%
“…Following methods used in psychology to study individual intelligence, Woolley et al [8] investigated the possibility of a collective intelligence factor: a latent factor describing a team's general ability to perform on a wide variety of tasks. They brought teams into the laboratory, had them perform a wide variety of tasks [6,9], and found that a team's performance on one type of task was closely related to its performance on all types. When they calculated a collective intelligence score based on the team's performance on the set of tasks, they found that it was only moderately related to the individual members' intelligence scores and was more predictive of future team performance than was individual members' average intelligence score [8] A series of studies have revealed factors related to collective intelligence, providing some insight into how to more reliably cultivate smart teams.…”
Section: Collective Intelligencementioning
confidence: 99%
“…However, decades of research by social psychologists have provided explanations for the less-than-ideal performance of most social groups. "Process loss" saps the resources provided by individual members through coordination failures (Steiner, 1972), social loafing (Latané, Williams, & Harkins, 1979), groupthink (Janis, 1972;Turner & Pratkanis, 1998), and interpersonal competition (McGrath, 1984).…”
Section: Accuracy As a Criterion For Good Group Decision Rulesmentioning
confidence: 99%
“…Team behavior depends on the demands of the task itself, and teams can be categorized into distinct types on the basis of these tasks (McGrath, 1984). One particularly common type of team (and the focus of the present investigation) is production and service teams.…”
Section: Team Routines and External Team Leader Interventionmentioning
confidence: 99%